Peristalsis-like migration of carbon-metabolizing catalytic nanoparticles. (November 2021) - Lu, Peng-Han; Xie, De-Gang; Liu, Bo-Yu; Ai, Fei; Zhang, Zhao-Rui; Jin, Ming-Shang; Zhang, Xiao Feng; Ma, En; Li, Ju; Shan, Zhi-Wei
Abstract: Translational and rotational motion of solid matter is normally driven by external physical forces. Here we report that under oxygen atmosphere inside an environmental transmission electron microscope, catalytic palladium nanoparticles underwent a self-propelled, peristalsis-like locomotion on a supporting substrate at a relatively low temperature. Surprisingly, the particles maintained crystalline interior and even conserved their initial crystal orientations during the dramatic liquid-like motion. Such "peristaltic" crystal migration with shape oscillation is found to be mediated by profuse surface diffusion, under chemical driving forces from palladium-catalyzed gaseous oxidation of a carbonaceous layer. These findings open a new avenue of efficient heterogeneous catalysis, and reveal emergent behavior that can arise out of an energy-metabolizing nano-system.